2020
DOI: 10.1002/wer.1433
|View full text |Cite
|
Sign up to set email alerts
|

Medical laboratory wastewater treatment by electro‐fenton process: Modeling and optimization using central composite design

Abstract: Medical laboratory wastewaters arising from diagnosis and examination units show highly toxic characteristic. Within the scope of the study, removal of the wastewater’s toxicity and increasing BOD5/COD ratio of the medical laboratory wastewaters through electro‐Fenton (EF) process were investigated. In the study, central composite design was applied to optimize the process parameters of EF for COD, BOD5, and toxicity unit (TU) removal. Based on ANOVA, H2O2/COD was found to be significant parameter for COD remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Graphical pareto analysis is one of the tools used to see more clearly the effect of the experimental variables on the response functions. The percentage contribution of each variable to the removal efficiency and energy consumption was determined using the following Equation 11 (Basturk et al, 2021):…”
Section: Anova Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Graphical pareto analysis is one of the tools used to see more clearly the effect of the experimental variables on the response functions. The percentage contribution of each variable to the removal efficiency and energy consumption was determined using the following Equation 11 (Basturk et al, 2021):…”
Section: Anova Analysismentioning
confidence: 99%
“…Designed using electrochemical principles, these processes are of great interest due to their ability to ensure environmental compatibility (Ismail et al, 2021). The electro-Fenton process, which has gained attention in recent years, is an economical and environmentally friendly process that can be used to efficiently remove toxic and/or persistent organic pollutants such as pharmaceuticals (Basturk et al, 2021, Dolatabadi and Ahmadzadeh, 2019, Liu et al, 2023, Shoorangiz et al, 2019, dyes (Cruz-González et al, 2012, Iranpour et al, 2018 and phenols (Al-Zubaidi andPak, 2020, Rahmani et al, 2015) from water.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing environmental awareness and the fact that countries have targets for environmental sustainability necessitate the efficient and environmentally friendly treatment of industrial wastewater. Electro-Fenton process, which is one of the advanced oxidation methods meeting these criteria, can be used to effectively remove toxic and/or persistent organic pollutants (Basturk et al, 2021;Dolatabadi & Ahmadzadeh, 2019;Liu et al, 2023;Shoorangiz et al, 2019), dyes Iranpour et al, 2018) and phenols (Al-Zubaidi & Pak, 2020) from water.…”
Section: Introductionmentioning
confidence: 99%
“…Today, many advanced oxidation processes are successfully applied in many treatment facilities (Ulucan-Altuntas and Ilhan, 2018;Basturk et al, 2020;Can-Guven et al, 2020). From this viewpoint, the Fenton process is used as the most common oxidation process (Zhang et al, 2017;Han et al, 2020;Lai et al, 2020), and several authors have reported that ozone (Li et al, 2008), UV (Yan et al, 2020), photocatalytic membrane reactors (Espíndola et al, 2019) are also effective for OTC degradation.…”
Section: Introductionmentioning
confidence: 99%